Analisis dan Evaluasi Website Fakultas Sains dan Teknologi Sebagai Sistem Informasi Layanan Akademik - Mellyana Rafizah (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2026)
A faculty website serves as vital infrastructure in supporting the digital transformation of higher education institutions. However, many academic portals currently remain static and limited to one-way information dissemination. This study aims to analyze and evaluate the quality of the Faculty of Science and Technology website as an academic service information system. A comprehensive system evaluation was conducted by integrating the WebQual 4.0 model and the PIECES Framework to assess quality across usability, information quality, service interaction, performance, economy, control, efficiency, and service domains. The research adopted a descriptive quantitative approach, with data gathered via direct observation, literature reviews, and structured questionnaires using a 1–5 Likert scale distributed to platform users. The empirical results demonstrate that the website functions adequately as a basic academic information provider. Nonetheless, significant deficiencies were identified regarding inconsistent content updates, a lack of two-way interactive service features, and limited data access security controls. Consequently, this study formulates structural optimization recommendations, including responsive user interface and experience (UI/UX) redesign, strengthening internal access control management, and full academic system integration to cultivate a transparent and adaptive digital service ecosystem tailored to the needs of the modern academic community.